Leadership in Action : Issues and Observations - In Organizations, It Takes All Kinds - Ginnett, Robert C. (Center for Creative Leadership, 2001)
The most encouraging news is that research has shown that no matter whether one leans toward managing, leading, or neither, both sets of skills can be learned with effort and over time.